Humanized Mouse as a Tool to Predict Immunotoxicity of Human Biologics - Yong, Kylie Su Mei; Her, Zhisheng; Tan, Sue Yee; Tan, Wilson Wei Sheng; Liu, Min; Lai, Fritz; Heng, Shi Min; Fan, Yong; Chang, Kenneth Tou En; Wang, Cheng-I; Chan, Jerry Kok Yen; Chen, Jianzhu; et al. (Frontiers in Immunology, 2020)
Advancements in science enable researchers to constantly innovate and create novel biologics. However, the use of non-human animal models during the development of biologics impedes identification of precise in vivo interactions between the human immune system and treatments. Due to lack of this understanding, adverse effects are frequently observed in healthy volunteers and patients exposed to potential biologics during clinical trials. In this study, we evaluated and compared the effects of known immunotoxic biologics, Proleukin®/IL-2 and OKT3 in humanized mice (reconstituted with human fetal cells) to published clinical outcomes. We demonstrated that humanized mice were able to recapitulate in vivo pathological changes and human-specific immune responses, such as elevated cytokine levels and modulated lymphocytes and myeloid subsets. Given the high similarities of immunological side effects observed between humanized mice and clinical studies, this model could be used to assess immunotoxicity of biologics at a pre-clinical stage, without placing research participants and/or patients at risk.